Establishing a community advisory group (CAG) for partnership defined quality (PDQ) towards improving primary health care in a peri-urban setting in KwaZulu-Natal, South Africa - Thoko Ndaba; Myra Taylor; Musawenkosi Mabaso (BMC, 2020)
Abstract Background Community advisory groups (CAGs) have been shown to be catalysts who bridge the gap between communities and primary health care facilities by sustaining good working relationships through community engagement to improve the quality of the health care services. This study aimed to explore the establishment, operation, and accomplishments of a CAG towards building a strong partnership between the health facilities and local communities in support of the Partner Defined Quality (PDQ) process, to improve the delivery of quality maternal and neonatal care in a peri-urban setting in the province of KwaZulu-Natal, South Africa. Methods The study used a qualitative exploratory research design. Recruitment followed a purposive sampling approach. The study targeted leadership representatives from the community, potential beneficiaries, and health care providers in the selected catchment areas. Participants were identified during community mobilization events that took place during the preparatory stage to ensure key stakeholder support. A participatory research approach was used to discuss membership, composition, the selection criteria, including formulation, and agreement on terms of reference of the CAG membership, roles and responsibilities. A rapid assessment method was used for data collection and analysis of establishment of the CAG, its activities and accomplishments. Results The community nominated 24 CAG members during the consultative meetings and the organogram provides clear terms of reference, roles and responsibilities. Immediately after inception, the CAG used four indicators (weaknesses, threats and risks, strengths, and opportunities) to review the community and primary health care challenges that affect their communities. These CAG activities were linked with the phases of the PDQ process. The CAG committed itself going forward to continue to create an enabling environment for all stakeholders working to improve the well-being of the community, especially the PDQ teams working on improving the care of pregnant mothers and their babies pre- and post-delivery. Conclusion This work shows that developing community relationships and infrastructure are critical initial stages before embarking on PDQ planning and implementation. Empowerment, local ownership, funding, technical resources and ongoing support are critical elements for sustainability of CAG activities.